2019
DOI: 10.1097/sla.0000000000002475
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Procedural Trends for Renal Trauma Management

Abstract: National trends for procedural management of renal trauma are toward less invasive interventions. These trends suggest favorable change towards renal preservation and decreased morbidity, potentially facilitated, in part, by improved radiographic staging and endovascular techniques, and also increased provider awareness of the safety and value of conservative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…This may be partially due to changes in road safety regulations and behavioral patterns [21,22]. Regarding the management of blunt renal trauma, we observed an increase in the use of emergency abdominal angiography and a decline in nephrectomy, which is a similar trend to Western countries [6,7,23]. The mortality rate decreased from 15.3 to 7.3% over 15 years, which is a similar trend to previous studies [24].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This may be partially due to changes in road safety regulations and behavioral patterns [21,22]. Regarding the management of blunt renal trauma, we observed an increase in the use of emergency abdominal angiography and a decline in nephrectomy, which is a similar trend to Western countries [6,7,23]. The mortality rate decreased from 15.3 to 7.3% over 15 years, which is a similar trend to previous studies [24].…”
Section: Discussionsupporting
confidence: 83%
“…5 Kyoto University Health Service, Kyoto, Japan. 6 Department of Emergency Medicine, Kyoto Prefectural University of Medicine, Kyoto, Japan. 7 Department of Food Science, Faculty of Home Economics, Otsuma Women's University, Tokyo, Japan.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…21,22 Regarding the management of blunt renal trauma, we observed an increase in the use of emergency abdominal angiography and a decline in nephrectomy, which is a similar trend to Western countries. 6,7,23 The mortality rate decreased from 15.3 % to 7.3% over 15 years, which is a similar trend to previous studies. 24…”
Section: Discussionsupporting
confidence: 89%
“…4,5 In recent years, less invasive interventions, such as endovascular procedures, have increasingly been used for blunt renal trauma. 6,7 Nevertheless, nephrectomy is still required for unstable patients those in whom non-operative management fails. 8,9,10 According to a report by van der Wilden et al, among patients injured by road tra c accidents, non-operative management failed in 27.3% of the patients who were > 55 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Adjusted replaced the past tendency toward aggressive surgical exploration in select, well-staged, and hemodynamically stable cases [8,27,28]. The time trend of renal trauma management has recently been studied, but has not previously been evaluated at the level of tiered trauma systems or interfacility transfer [29]. We found that overall odds of morality were lower in those with level I transfers, compared with those managed at a non-level I trauma center.…”
Section: Crudementioning
confidence: 80%